Impact of Accounting Conservatism on Earnings Persistence at Non-financial Listed Firms on Vietnam Stock Exchange - Nguyen, Thanh Hung; Vu, Trong Quang (Archives of Business Research, 2025)
The article is conducted to examine the impact of accounting conservatism on the earnings persistence. In order to achieve the aim of research, the panel data set was compiled, collected, and calculated from the audited financial statements of more than 400 non-financial enterprises listed on the Vietnamese Stock Exchange in period from 2012 to 2022. We perform essential tests to assess the likelihood of model defects in research models such as heteroskedasticity, autocorrelation, heteroskedasticity. Besides, fixed effects model and robustness tests were employed to overcome endogeneity issues. The results indicate that the level of accounting conservatism positively impacts earnings persistence. This finding implies that profits at firms with highly conservative financial reporting are maintained and forecasted to be more stable in future years than those at less conservative firms in accounting. Our findings provide valuable empirical evidence that implementing the prudence principle in accounting enhances the overall quality of financial statement information, particularly the quality of earnings as reflected through earnings persistence. Furthermore, the research findings provide a practical foundation for auditors at listed firms to advise, monitor, and fulfill their professional roles in guiding or requiring listed companies to adopt a higher degree of accounting conservatism.